Pola Sebaran Karbon Monoksida Akibat Aktivitas Kendaraan Bermotor: (Studi Kasus Jalan Cristina Martha Tiahahu) - Syaharian, Lini; Assiddieq, Moch.; Sumarlin, Sumarlin (Universitas Muhammadiyah Kendari, 2024)
Air pollution is the entry or inputs of foreign particles resulting in a change in the air concentration from the normal concentration. A carbon monoxide spread pattern model can be calculated using the Gaussian equation, where this equation can calculate a particular concentration of particles at a specified distance as well as describe a pattern of the spread of the area of the research site and its source. The focus of this research was carried out in the street Cristina Martha Tiahahu Kelurahan Lepo-lepo city of Kendari by counting the number of vehicles, dispersion and concentration of carbon monoxide and modeling using Argis. The number of vehicles contributing to the CO emission rate of 32863.22 μg/km.s on Sunday, 44175.33 micrograms/km./s on Monday and 35467.11 microgram/km/s on Thursday. Based on Guass calculations the highest concentration of carbon monoxide spread is at a distance of 0.5 m from the source of emissions of 6,21716 microgramm/m3 on Thursday, 5,35059 microgramme/m3, on Sunday and 3,24231 microgrammes/m3. With an average wind speed of 3 m/s and northeast winds. Spatial analysis with modeling on Arcgis showed the area of impact spread from CO gas pollution to the area around the highway.